Fabric sourcing practices for women's woven tops of selected garment companies - Flores, Mylene Elda Adaba
A descriptive study was conducted to know the fabric sourcing practices for women's woven tops of selected garment companies, specifically in the Quezon City and Pasig areas only. Data were collected through a survey conducted using guided interviews as the research instruments. Through convenience sampling, two respondent companies from Quezon City and Pasig, totaling to four respondent companies, participated in the study. This was conducted from the mid-pat of January until the end of February of 2007. The results showed that all four respondent companies consider price and quality when it comes to sourcing fabrics. The quantity and modes of payment only came second. Aside from this information, the most sourced and ordered woven fabric was cotton twill. Poplin was the second ordered woven fabric. The third most were stripes, checks, muslin and linen fabrics. The garment companies indicated that they choose their fabric suppliers for their price points, quality of goods, free fabric samples, professionalism and goo relations. The common factor among all four respondent companies in terms of the fabric souring procedures used was their constant requests for fabric samples. All four respondent companies also considered sourcing, ordering and buying of fabrics abroad. Credit and cash on delivery were preferred as modes of payment. The study was also able to determine the following common problems encountered through fabric sourcing: a) fabric defects, b) delayed deliveries, c) and wrong fabrics. When these problems are encountered, these are either solved by having the fabrics returned, replaced with penalties and/or getting discounts from the supplier.